Physiological responses of fig fruit to non-wounding vibration - MAO Lin-chun; YE Li-yang (浙江大学学报. 农业与生命科学版, 2000)
Respiration rate, ethylene production, cellular leakage and superoxide dismutase (SOD) activity in fig (Ficus carica L. cv. Masuidauphine, Brunswick) fruit were investigated after the treatment of non-wounding vibration. Treatments of non-wounding vibration for 10 min at the force of 4.0×g induced the increases of respiration rate, ethylene production, cellular leakage and SOD activity in fig fruit. The accelerated physiological activities induced by vibration were partially recovered beginning from the 4th day after vibration, suggesting that a recovery mechanism resisting to the vibrational stress might exist in detached fruit. Masuidauphine was more susceptible to vibration than Brunswick. It might be probable that the physical properties of fig fruit had more influences on their susceptibility to vibration than the physiological characteristics did.